Karakteristik Marshall Dalam Aspal Campuran Panas AC-WC Terhadap Variasi Temperatur Perendaman - Leily Fatmawati (Politeknik Negeri Semarang, 2013)
Road roughness layer construction work in Indonesia as long as this concern, i.e. damaged before age plans, although not all of these statements are valid in General. As an indication of overload or cause factor is often referred to by Physical Damage Factor (P.D.F.), time loaded and environmental change or the drainage function is not optimal. All three of these factors as the cause of the occurrence of the damage. The use of a material with a better quality of aggregate gradation of mainly filler material as well as asphalt binder material, as well as planning, quality of execution and how strict scrutiny. This research was conducted to measure up to the temperature influence of roughness asphalt macadam on the mixture of hot mix asphalt AC-WC using hard asphalt (Asphalt Pen 60/70) about Marshall characteristics and the result expected can provide information of Department of Public Work. In the study done of making test with variations in soaking temperature for analyzing how performance degradation when soaking temperature paved mixture does not fit standard (standard temperature of 60° C).